Halal traceability study chicken meat nuggets - Nurhayati, Ima; Khoiroh, Naimatul (Universitas Airlangga, 2023)
Indonesia is a country with a majority Muslim population, so this can cause concern. Islam also teaches about the obligation to consume halal food, resulting in the emergence of various halal industries to meet food needs. One of the products produced by the halal food industry is chicken nuggets. Chicken nuggets are available in various brands with different ingredients ranging from raw materials, additional ingredients, to supporting ingredients. When processing nuggets, it must be ensured that they meet halal food safety standards, one of which is using the Halal Critical Control Point (HCCP) approach. This HCCP aims to consider the origin of raw materials, the processing process until it becomes a product that is ready for distribution. This research aims to determine the critical point for halal food in chicken nugget products in Indonesia as a novelty of this research. In this research, a library study or literature review research method was used. The results of this search show that the critical point for halal food in chicken nuggets is divided into 7 of them; 1) chicken meat, 2) wheat flour, 3) cooking oil, 4) processed vegetable ingredients, 5) sugar, 6) soy protein, 7) monosodium glutamate. This research can help provide information to the public about the importance of halal food from production to processing aspects.